P1-S4.26 Duration, incidence and prevalence of Chlamydia trachomatis in women: estimation by multi-parameter synthesis. (10th July 2011) - Price, M; Ades, A E; De Angelis, D; Welton, N; Macleod, J; Soldan, K; Turner, K; Simms, I; Horner, P
Abstract : Background: An understanding of the prevalence and incidence of Chlamydia trachomatis (CT) infection is needed to assess the potential value of screening. Typically, the estimation of incidence, prevalence and duration are seen as distinct exercises. Here we estimate them simultaneously from the available data subject to the well-known relationship prevalence = incidence times duration. Methods: We re-examine studies of duration of asymptomatic CT, based on recent reviews, and propose a model. Information from a recent synthesis of UK prevalence studies, and data on infection and re-infection rates in UK clinic settings, are used to generate estimates of incidence of infection in the general population, taking account of the effect of duration of infection on observed incidence. We use Bayesian multi-parameter evidence synthesis to check the consistency of the evidence and to produce internally coherent estimates of duration, incidence and prevalence in women. Results: The three sets of evidence sources that directly inform incidence, prevalence and duration respectively were consistent with each other. Our estimates are: duration of asymptomatic infection 1.25 years (1.04, 1.50), average incidence and prevalence in 16–44 year olds 2.2% (1.7, 2.9) per year and 2.1% (1.7, 2.6) respectively. Conclusions: The apparently heterogeneous estimates of duration of asymptomatic CT in the literature are explained by the different study designs. Adapted appropriately, they agree with UK prevalence and incidence data.